2020
DOI: 10.1111/are.14960
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, nucleic acids, leptin and adiponectin and their receptor gene expression were significantly affected by feeding different lipid supplementation in GIFT tilapia juveniles

Abstract: The experiment was to investigate the effect of different dietary lipid levels on the growth performance, nucleic acids, leptin and adiponectin as well as their receptor gene expression in juvenile genetically improved farmed tilapia (GIFT, Oreochromis niloticus). Six groups of the juveniles with 40 days of age in triplicate were fed for 90 days using 6 iso‐nitrogen (34% dietary protein) diets. The 6 diets were control diet contained 0.35% of lipid, without lipid supplementation, and the other diets were added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…Alanyl‐glutamine dipeptide (Yoon et al, 2020; Yu et al, 2016; Zhang et al, 2022) and VE (Noguchi, 2019; Zhou et al, 2013) were reported to improve fish growth. The same results were obtained in marine juvenile cobia ( Rachycentron canadum ) (Ding et al, 2017, 2018) and freshwater farmed tilapia (GIFT, Oreochromis niloticus ) (Ding et al, 2021; Xu, Zheng, et al, 2020). (2) Alanyl‐glutamine dipeptide and/or VE might improve the antioxidant indexes of fish.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Alanyl‐glutamine dipeptide (Yoon et al, 2020; Yu et al, 2016; Zhang et al, 2022) and VE (Noguchi, 2019; Zhou et al, 2013) were reported to improve fish growth. The same results were obtained in marine juvenile cobia ( Rachycentron canadum ) (Ding et al, 2017, 2018) and freshwater farmed tilapia (GIFT, Oreochromis niloticus ) (Ding et al, 2021; Xu, Zheng, et al, 2020). (2) Alanyl‐glutamine dipeptide and/or VE might improve the antioxidant indexes of fish.…”
Section: Discussionsupporting
confidence: 63%
“…The RNA/DNA ratio could accurately evaluate the short‐term and long‐term growth status of fish (Grimm et al, 2015; Gupta et al, 2015). The ratio of RNA/DNA is an important indicator of growth, well‐being, and nutritional condition in sea fish (Ding et al, 2009; Xu et al, 2009) and freshwater fish (Ding et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of antioxidant‐related genes in the livers of the fish was determined following the method of Ding et al (2021). Briefly, 500 ng of total RNA extracted from samples was reverse‐transcribed individually into cDNA using the Steady Pure Universal RNA Extraction Kit and Evo M‐MLV reverse transcription kit (Accurate Biology Bio‐technology Engineering Ltd., Changsha, China).…”
Section: Methodsmentioning
confidence: 99%
“…Lipid, as one of the most essential nutrients for fish, plays a crucial role in their growth, development, and metabolism [1]. Lipid not only provides energy for fish but also serves as an important component of their bodies [2]. However, both excessive and insufficient levels of dietary lipid supplementation can have inhibitory effects on growth, development, and disease resistance [3].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic improvement-farmed tilapia (GIFT, Oreochromis niloticus) is an important commercially cultured species worldwide and known for its strong disease resistance, fast growth rate, high nutritional value, and low-cost feed ingredients [2]. Considering the omnivorous nature and economic significance of GIFT tilapia, this study selected GIFT tilapia as the experimental fish.…”
Section: Introductionmentioning
confidence: 99%